2004
DOI: 10.1016/j.clpt.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Diflomotecan pharmacokinetics in relation to ABCG2 421C>A genotype*1

Abstract: These findings provide the first evidence linking variant ABCG2 alleles to altered drug exposure and suggest that interindividual variability in substrate drug effects might be influenced, in part, by ABCG2 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(137 citation statements)
references
References 19 publications
10
120
3
4
Order By: Relevance
“…Heterozygotes exhibited significantly higher plasma concentrations of diflomotecan after intravenous administration, whereas the plasma concentration-time profiles were similar after oral administration [70]. Such a discrepancy cannot be explained from a pharmacokinetic viewpoint, and the effect of such a polymorphism on the plasma concentration should be theoretically clearer after oral administration.…”
Section: Polymorphisms Of Abcg2mentioning
confidence: 89%
“…Heterozygotes exhibited significantly higher plasma concentrations of diflomotecan after intravenous administration, whereas the plasma concentration-time profiles were similar after oral administration [70]. Such a discrepancy cannot be explained from a pharmacokinetic viewpoint, and the effect of such a polymorphism on the plasma concentration should be theoretically clearer after oral administration.…”
Section: Polymorphisms Of Abcg2mentioning
confidence: 89%
“…ABCB1 appears to be the main paclitaxel transporter 23,24 and variants in ABCB1 have been demonstrated to alter P-glycoprotein expression. 25,26 A nonsynonymous variant in ABCG2 (421C4A; Q141K) has been associated with drug resistance in vitro and in vivo, [27][28][29] and with survival in prostate cancer patients receiving docetaxel chemotherapy (P ¼ 0.05), 30 consequently, despite the lack of evidence associating taxane transport with ABCG2 the 421C4A variant was included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…(14) We also reported variant BCRP SNP cDNAs harboring 421C>A (amino acid substitution Q141K), (15) and this SNP is physiologically important because the pharmacokinetics of diflomotecan, a new camptothecin-derivative anticancer agent, and the risk of adverse reactions, such as gefitinib-induced diarrhea, was affected in patients heterozygous for the A421 allele. (16) In addition, we reported that a germ-line mutant allele 1291T>C expresses the F431L variant of BCRP with lower functional resistance to SN-38. (17) This suggests that amino acid substitution F431L may affect substrate recognition of SN-38.…”
mentioning
confidence: 99%